Revitalization Strategy for Local Wisdom as an Effort to Improve Tourism Destination in Jember Regency - Permatasari , Yovita Dyah; Sholihah, Mar’atus; Ratnasari, Khur’in In (Proceedings of Annual Conference on Community Engagement, 2022)
the income value at Jember Regency tourism sector has decreased drastically since Covid-19 spread to the world. WHO (World Health Organization) declaration was a start to cause this effect which applies health protocols to overcome and prevent the spread of Covid-19. One of them is to avoid crowds or social distancing and prohibit all forms of socialization in a public area. As a result, the local community lifestyle has changed significantly, and even the local community routine activities are also very limited. The purpose of this community development is to explain; what, why, and how the strategy to revitalize local wisdom as an effort to increase tourism destinations in Jember Regency. The method that is applied is EBR (Empowerment Based Research). The analysis that is applied is SWOT (Strength, Weakness, Opportunity, and Treatment) to analyze the results of local cultural studies. The results of this community development show that local wisdom context in community activities integrated with religion can create a new nuance with the theme " “Pancasila as My Village” in a local cultural performance event, namely in Sukoreno Village, and Sidorejo Village, Umbulsari District, Jember Regency.